Business statistics in practice - Bowerman, Bruce L.; O'Connell, Richard T.; Hand, Michael L. (Boston : McGraw-Hill/Irwin, 2001)
Mathematics and Statistics
Keywords: Business statistics; Commercial statistics; Applied statistics